CGIAR Food Systems Accelerator Program – Endline Evaluation Report - Lozano, Denise; Dam Lam, Rodolfo; Zulu, Mercy; Rossignoli, Cristiano (WorldFish, 2023)
This report presents the findings of the endline evaluation study conducted at the conclusion of the first cohort of the CGIAR Food Systems Accelerator (CFSA) program. This study seeks to identify the progress in the attainment of specific capabilities and resources by the founders of the Agribusiness Partners (AP) through the technical assistance received, their general satisfaction, and overall feedback regarding their participation in the program.